Shirat ha-ʿatsabim - Dayan, Yehonatan (Resling, 2022)
Brenner's place in the Hebrew story tradition is a place of shadows. A place of others, grief and hard truth. Both in the short and charged plot of his life and in his literary work, he is Melancholy, the Black Martha of Hebrew literature. Brenner's stories express the taga of things. Their roots come from the depth of the Hebrew word, from the heart of the enterprise and the Zionist dream, as well as from the history of the modes of melancholic expression: the message of the degree of sorrow in existence. In melancholic poetics lies the complexity, explosiveness, complexity and sublimity of the Bernari text. In The Poetry of the Nerves, Yonatan Dayan speaks of melancholy as a human and literary quality, as an existential condition and as a way of expression. These guide his reading in Brenner's melancholic expression as a harbinger of sorrow, as a knower of flaw and error, and this in a past tense that is being renewed as a world language, and from its renewal it announces its loss. But what is the nature of the message and what is unique about this Brenner - whose literature is written as an expression of loss, the lamented Brenner - the author demands in many midrashims from world and Hebrew literature; From the myth of the melancholic Saturn, from the teachings of Hippocrates, from Aristotle's mistakes, from the poets of the Psalms, from Robert Burton's letters, from Walter Benjamin's theory of the Toga play, from Freud's pathologies and many others. All of these merge when reading Brenner's works:
Literaturangaben, Seiten 288-283
Keywords: Criticism; interpretation; etc; Brenner; Joseph Ḥayyim; Brenner; Yôsēf Ḥayyîm; Literatur; Neuhebräisch; Melancholie; Melancholy in literature; Hebrew fiction; Themes; motives